Utilization of Recycled Concrete Aggregates in Stone Mastic Asphalt Mixtures - Mohammad Saeed Pourtahmasb; Mohamed Rehan Karim (Advances in Materials Science and Engineering)
Recycled concrete aggregate (RCA) is considered as one of the largest wastes in the entire world which is produced by demolishing concrete structures such as buildings, bridges, and dams. It is the intention of scientists and researchers, as well as people in authority, to explore waste material recycling for environmental and economic advantages. The current paper presents an experimental research on the feasibility of reusing RCA in stone mastic asphalt (SMA) mixtures as a partial replacement of coarse and fine aggregates. The engineering properties of SMA mixtures containing RCA have been evaluated for different percentages of binders based on the Marshall mix design method. The outcomes were statistically analyzed using two-factor analysis of variance (ANOVA). Test results revealed that the performance of SMA mixtures is affected by RCA due to higher porosity and absorption of RCA in comparison with virgin granite aggregates. However, the engineering properties of SMA mixtures containing a particular amount of RCA showed the acceptable trends and could satisfy the standard requirements. Moreover, to achieve desirable performance characteristics, more caution should be made on properties of SMA mixtures containing RCA.